Clonidine Overdose as an Unusual Cause of Heart Failure - Jagdeep Bhullar PharmD; Arti Patel MS4; Jaagruthi Chitithoti DO; Frederick Venter MD; Theingi Win MD; Fowrooz Joolhar MD (SAGE Publishing, 2022)
Clonidine is used as an antihypertensive medication due to its effect on decreasing peripheral vascular resistance and therefore lowering blood pressure. Alpha antagonism in the medulla and the posterior hypothalamus causing a reduction in sympathetic activation allows for clonidine to be used as an effective off-label treatment for attention-deficit/hyperactivity disorder (ADHD). This is a case of a 28-year-old female with hypertension, ADHD, and depression who developed acute heart failure with significant troponemia after ingesting 30 pills of clonidine. We illustrate the possible rare diagnosis of systolic heart failure and coronary vasospasm secondary to clonidine overdose.